Identifikasi Muka Air Tanah Berdasarkan Data Resistivitas dan Geologi di Nagari Taram - Ilham Habib; Dipo Caesario (Universitas Negeri Gorontalo, 2025)
This study aims to identify the distribution and depth of the groundwater table in Nagari Taram by integrating resistivity data from the Schlumberger geoelectrical configuration with local geological information. Six (6) Vertical Electrical Sounding (VES) measurements were acquired across different land units to capture variations in subsurface resistivity. The resistivity data were processed through 1D inversion to interpret lithology and layer thickness, which were subsequently correlated with regional geological maps to confirm the characteristics of water‑bearing formations. The results indicate that shallow aquifers generally occur at depths of 5–20 meters with resistivity values ranging from 30 to 150 Ω·m, representing sandy layers to weathered conglomerate of the Brani Formation or young alluvial deposits. Clay and tuff layers with low to very high resistivity act as aquicludes and aquifuges, serving as barriers to groundwater flow. Variations in groundwater table depth across the sites are influenced by geomorphological conditions and surface sediment thickness. The integration of resistivity and geological data provides more accurate information for delineating shallow aquifer zones, supporting groundwater utilization for domestic and agricultural needs in Nagari Taram.